Participatory Decision Making in Homestay Waste Management to Support Sustainable Tourism Development at Sakera Beach Bintan, Indonesia - Widi Hardini; I Nyoman Budiartha; Violetta Cherryline; Asman Abnur; Hari Sandi Atmaja; Agung Edy Wibowo; Nensi Lapotulo; Socrates (Industrial and Domestic Waste Management, 2026)
This study explored the participatory decision-making process in homestay waste management to support sustainable tourism development at Sakera Beach, Bintan. Despite the dual function of homestays in generating organic, plastic, and liquid waste, waste management practices remained rudimentary and relied primarily on mixed-waste collection. A qualitative approach with a case study design was employed, and data were collected through field observations, in-depth interviews with eleven key stakeholders, and documentation. The findings revealed that although stakeholders, including homestay owners, the local community, the tourism awareness group (Pokdarwis), and the local government, demonstrated basic environmental awareness, their participation was predominantly situational and lacked a formal structure. The effectiveness of waste governance was constrained by several significant barriers, including the absence of shared regulations, inadequate waste-sorting facilities, informal coordination mechanisms, and limited guest education. To address these systemic gaps, this study proposed a collaborative waste management strategy that emphasized source-based waste segregation, reduction of single-use plastics, organic composting, informative guest education, and a coordinated waste collection schedule. The study concluded that transitioning from reactive, individual initiatives to a structured, collaborative governance framework was essential for mitigating coastal pollution and ensuring the long-term environmental and economic sustainability of the Sakera Beach tourism destination. However, because this study primarily proposed a conceptual framework based on qualitative findings, future empirical research is needed to quantitatively evaluate its implementation and investigate feasible financial incentive mechanisms for homestay owners.